THE EFFECTIVENESS OF PSYCHOLOGICAL SKILLS TRAINING PROGRAM ON NETBALL SHOOTING PERFORMANCE - Shaari, Jamatul Shahidah; Hooi, Lim Boon; Siswantoyo, Siswantoyo (Jurnal Cakrawala Pendidikan, 2019)
The study was aimed to investigate the effect of Psychological Skills Training Program on netball shooting performance. The experimental method was used on three groups of an 8-week intervention: combination of diaphragmatic breathing and imagery, plus physical practice (G1); combination of DB and self-talk, plus physical practice (G2); and control group which have physical practice only (G3). A SPANOVA was conducted to assess the impact of all groups on shooting performance across the two time periods. The main effect comparing the two treatments and a control group was significant, p .001. Post hoc Tukey test differ significantly at p .05. However, the G2 was not significantly different from the G3. The results indicated that netballers of different skill used of PST, either G1 or G2 were found to improve the netball shooting performance. It was also showed that G1 has better netball shooting performance rather than G2 and G3. As to highlighting, that the principles and practical applications of these most basic psychological skills can be taught in easier ways and probably in a relative short period of time among youth athletes.